Faktor-Faktor Yang Menentukan Audit Judgment - Pardomuan Ritonga; Henny Mulyati (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
This research was aimed to examine the effect of auditor experience, pressure obedience, tax complexity, and auditor expertise to audit judgment empirically. The sample of this research are auditors who worked on Public Accountant Firm (KAP) Representative of DKI Jakarta Province. The example was conducted by purposive sampling method. Collecting data was performed by a questionnaire distributed directly to auditors as much as 108 questionnaires. Data analysis used multiple linear regression methods with SPSS (Statistical Product and Service Solution) 23.00 Version. The result of this research showed that auditor experience, pressure obedience, tax complexity, and auditor expertise by simultaneously and partially have a significantly positive effect on the audit judgment.